Pauses during a writing process in two typologically different languages - Ivaska Ilmari; Toropainen Outi; Lahtinen Sinikka (ARLE (International Association for Research in L1 Education), 2025)
This study investigates how pausing behaviour within a writing session is associated with the writer's language proficiency, focusing on Finnish and Swedish as both first language (L1) and learner language (L2). The data were collected through keyboard logging software and evaluated using CEFR-based assessments of the resulting texts. The relationship was analysed using ordinal mixed-effects logistic regression modelling, where proficiency is modelled as a function of various variables related to pausing behaviour. The results show that the L2 writing process reflects the writer's proficiency. However, there is a significant difference between L2 writers of Swedish and L2 writers of Finnish compared to L1 writers. The advanced L2 writers of Swedish behave similarly to the L1 Swedish writers. In contrast, even the most advanced L2 writers of Finnish have pause lengths and linguistic contexts that are more similar to the less advanced L2 writers than the L1 writers. In addition, the pauses between words do not indicate any clear proficiency-related patterning, leaving only within-word pauses as a robust indicator of proficiency, especially in Swedish. Unlike most writing process research, this study's parallel design allows for contrasting two typologically diverging languages while controlling for other contextual variables. Future studies could explore the grammatical nature of pause locations across the analysed languages.